2011
DOI: 10.1007/s10600-011-9877-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and physicochemical properties of cationic starches

Abstract: 547.458.61:661.185.232 N. S. Butrim, and T. L. YurkshtovichThe reaction kinetics of an aqueous suspension of potato starch, various amounts of NaOH, and cationic 3-chloro-2-hydroxypropyltrimethylammonium (chloride) were studied in detail. It was found that the compositions of the sparsely substituted cationic starch ethers and the efficiency of the reaction depended strongly on the ratio of components in the alkylating mixture. The physicochemical properties of the synthesized samples were studied using chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Wilson (2005) mentions that early attempts in the 1950s to add cationic starch at the size press were unsuccessful, and it had been suggested that the problems were due to the electrostatic interactions with the fiber surfaces. To prepare cationic starch, the suspension of starch grains is treated under highly alkaline conditions with epoxypropyl-trimethylammonium chloride or a related compound (Bergh and Hemmes 1991;Butrim et al 2011). Subsequent cooking of such starch yields molecular chains that have an affinity for cellulosic surfaces.…”
Section: Cationic Starchmentioning
confidence: 99%
“…Wilson (2005) mentions that early attempts in the 1950s to add cationic starch at the size press were unsuccessful, and it had been suggested that the problems were due to the electrostatic interactions with the fiber surfaces. To prepare cationic starch, the suspension of starch grains is treated under highly alkaline conditions with epoxypropyl-trimethylammonium chloride or a related compound (Bergh and Hemmes 1991;Butrim et al 2011). Subsequent cooking of such starch yields molecular chains that have an affinity for cellulosic surfaces.…”
Section: Cationic Starchmentioning
confidence: 99%
“…Chemically, the negative charge of the starch is converted into a positive charge. Commonly used reagents include 2-chloroethyldiethylamine, 2,3-epoxypropyldiethylamine, and 3-chloro-2-hydroxypropyl [11]. The charge of fibers can be balanced out by cationic starch.…”
Section: Introductionmentioning
confidence: 99%
“…The result is a positively charged starch, usually presented in dry powder form [ 13 ]. It is used for various functionalities such as emulsification and dry strength, as a flocculating agent [ 22 ], and in addition to negatively charged cellulose, paper, textiles, cosmetics, and others [ 23 ].…”
Section: Introductionmentioning
confidence: 99%